Overcoming the inequity of isolation : small grants and guided self-mobilisation for microenterprise development in rural Papua New Guinea : a thesis presented in partial fulfillment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Jennings, Shona (Massey University, 2003)
Stimulation of an informal sector is seen as a key strategy for poverty alleviation in many parts of the developing world, including Papua New Guinea. The stimulation of microenterprises within this sector aims at enabling the poor towards 'self-help'. The two pillars on which microenterprise stands are empowerment and finance, yet very isolated communities, such as those in the East Sepik Province of Papua New Guinea, often lack access to such enabling forces. In the absence of other financial opportunities, they sometimes apply to donor agencies for small grant funding as a means of accessing seed capital. Yet they are hampered in their efforts by low literacy, poorly developed infrastructure, the absence of organisations supporting microenterprise development, aid agency criteria, and isolation. Using Papua New Guinea as the field of reference, this paper initially looks at aid and microenterprise development, using literature to develop best practice understandings. These best practice understandings, which concentrate on issues to do with sustainability, appopriateness, viability and empowerment, accompany three tiers of knowledge (formal, common and perceptive) to form a framework. This framework helps assessors deliberate upon key topics in a way that incorporates praxis when making decisions concerning funding I then propose a workbook-style application form, that: 1) feeds appropriate information from the community back to the funder for use in the framework; 2) can be completed by people with very low literacy; and 3) leads a community through participatory exercises at both the village and household/clan levels, enabling them to analyse, plan and act in the ways they choose to and value.
Keywords: Papua New Guinea; Rural development; Finance; Small business